Nature-based interventions for bereavement care: a scoping review protocol. Issue 5 (19th May 2022) - Cleary, Anne; Dean, Julie; Pollock, Danielle; McDaid, Lisa; Boyle, Fran
ABSTRACT: Objective: The objective of this scoping review is to understand the types of nature-based interventions currently used in bereavement care and to map the theories of change explaining how such interventions may support bereavement care. Introduction: Bereavement can be associated with adverse psychosocial health outcomes. Nature-based interventions have been shown to have positive health and well-being outcomes, and offer diverse and flexible design and delivery options. However, this is an emerging field, and there is a need to explore the literature on the different types of nature-based interventions used in bereavement care and to identify the underpinning theories of change. Inclusion criteria: This review will include studies or reviews of participants who have experienced bereavement following the death of a loved one, and who have taken part in a nature-based intervention (eg, animal-assisted therapy, care farming, therapeutic horticulture, community gardens). Considering all nature contexts and geographic locations, this review will include studies that explore the role of nature-based interventions in bereavement care. Methods: Searches will be conducted in eight databases: Web of Science, Scopus, PubMed, PsycINFO, CINAHL, Social Science Database (ProQuest), PTSDpubs (ProQuest), and Research Library: Health and Medicine (ProQuest). Manual searches of reference lists of included full-text articles and keyword searches of prominent journals will be conducted. Data on the type of nature-based intervention, target sample, health outcomes, measures and methods used, and theory of change will be extracted from selected articles. The data extraction results will be presented in tabular format along with a narrative summary.